A Geographically-Based Land Use Suitability Assessment and Land Capability Classification - Cruz, Rex Victor O. (Arizona-Nevada Academy of Science, 1990)
From the Proceedings of the 1990 Meetings of the Arizona Section - American Water Resources Association and the Hydrology Section - Arizona-Nevada Academy of Science - April 21, 1990, Arizona State University, Tempe, Arizona